Managing Difficult Fractures due to Ballistic Trauma with Ilizarov Ring Fixation - Chand, Pankaj; Shrestha, Roshan Lal; KC, Bachu Ram; Shah, Bhanu Chand; Joshi, Amit; Thapa, Bishnu Nahadur (Medical Journal of Shree Birendra Hospital, 2010)
20 fractures (7 femoral and 13 tibial) were treated with the illizarov apparatus between 2003 to 2006. All were old injuries, previously managed by internal fixation (intramedullary rods), external fixation (Hoffman's external fixators), or conservatively with traction and plaster of paris slabs. Ilizarov fixators were applied to manage infected non-union with or without bone loss and malunion. Corticotomy and bone transport was carried out in cases with significant bone loss. In others without any limb shortening and minimal bony defect, bone grafting and compression was carried out. In one case valgus deformity along with non-union was corrected. Early weight bearing with range of motion exercises for ankle and knee joints were encouraged. Average fracture healing time was 12 months (8 to 18 months). All fractures healed with <5° of malalignment. Complications included pin site inflammation/ infection, muscle transfixation, knee and ankle joint stiffness and a wire fracture. The ilizarov device provided definitive fixation with acceptable results in all cases. Key words: Ilizarov ring fixator; distraction osteogenesis; bone transport; infective non-union; corticotomy DOI: 10.3126/mjsbh.v9i1.3482 Medical Journal of Shree Birendra Hospital Vol.9(1) 2010 1-8